1992
DOI: 10.2527/1992.70138x
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous oxytocin dilates the cervix in ewes

Abstract: Cervical anatomy in ewes usually prevents nonsurgical, intrauterine AI and transcervical embryo transfer (ET), which limits their commercial use in sheep. This study was conducted to determine whether oxytocin would dilate the cervix in ewes and permit passage of a stainless steel rod into the uterus. In Exp. 1, at 44 and 52 h after removal of progestogenated pessaries, ewes were injected i.v. with 0 (saline), 200, 400, or 600 USP units of oxytocin. Immediately before and after treatments, stainless steel rods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 0 publications
0
45
0
Order By: Relevance
“…Khalifa et al, [56] demonstrated that a stainless steel rod could be passed through the cervix into the uterus in 77% of ewes treated with 200, 400 or 600 USP of exogenous oxytocin injected i.v. ; the same rod could not be passed transcervically into the uterus of any saline-treated animals.…”
Section: Oxytocinmentioning
confidence: 99%
“…Khalifa et al, [56] demonstrated that a stainless steel rod could be passed through the cervix into the uterus in 77% of ewes treated with 200, 400 or 600 USP of exogenous oxytocin injected i.v. ; the same rod could not be passed transcervically into the uterus of any saline-treated animals.…”
Section: Oxytocinmentioning
confidence: 99%
“…This answer may be explained by effects of oxytocin that initiates collagenolytic enzyme process resulting in cervical dilation [19]. Previous studies showed that E 2 +OT or only OT [13,[20][21][22] caused cervical dilation in ewes. It has been proven that 400 IU OT led to dilation of cervix, but the injection of this amount of hormone right before the insemination may have some problems.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, hormonal strategy has been proposed to improve the efficacy of AI. Oxytocin and prostaglandin E (PGE) are effective hormones on cervix dilation [8,13,14]. Oxytocin and E 2 have no effects on luteal phase and have minimum injury when pipette is crossing the cervix during AI [8].…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…Oxytocin treatment caused relaxation of cervix and uterine catheter through the cervix have demonstrated that reduced the difficulty of the transition (Khalifa et al, 1992;Sayre and Lewis, 1996). The effect of oxytocin as a cervical dilator is different on the reproductive outcome in ewe.…”
Section: Oxytocinmentioning
confidence: 99%